Complex Circles of Partition and the Asymptotic Lemoine Conjecture : Asymptotic Lemoine Conjecture - Agama, Theophilus; Gensel, Berndt (My University, 2022)
Using the methods of the complex circles of partition (cCoPs), we study interior and exterior points of such structures in the complex plane. With simitarities to quotient groups inside of the group theory we define quo-tient cCoPs. With it we can prove an asymptotic version of the Lemoine Conjecture.
Keywords: interior point; exterior point; Bertrand postulate; prime number theorem; asymptotic; Lemoine